INCREASING THE ECONOMIC VALUE OF RECLAIMEDWOOD AND WASTEDWOOD THROUGH ENTREPRENEURSHIP AS A REAL OF ETHICAL BUSSINESS - Retno Susanti, Lamidi & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Kadipiro is a village in District Banjarsari, Surakarta. Along Solo-Purwodadi road ispart of Kadipiro, along the road, there are more than fifty SMEs (Small and MediumEnterprises) that cultivate raw material of teak. Every day, a lot of wasted wood isgenerated from their production process. So far the wasted wood is just dumped intofirewood for individuals or SMEs that need firewood such as tofu SMEs, crackersSMEs, etc. It is of course very unfortunate, moreover teak is a kind of wood with a verygood quality. By looking at the environment and its resources, actually the wasted woodcan become a commodity that has high competitiveness with people creativity andinnovation. Jati Lawas Alto Solo SME is a creative SMEs that produce sills, doors,furniture, gazebo and wooden house with reclaimed wood of former house, formertimber of ships as their raw materials. In terms of raw materials, this SME isenvironmentally friendly SME. Karang Taruna (Youth organization), MMIB, see selfemploymentopportunities of those much wasted wood. Those wasted woods are usedas raw material for their production. However, the limitations of the equipment andmanagement make the uptake of raw material from wasted wood that is utilized as acreative product is still low. Research and Implementation Team of Universitas SlametRiyadi (UNISRI), Jati Lawas Alto Solo SME and Group Organization MMIB initiatethe utilization of wasted wood into raw material resource for making creative productsand make it more optimized. By the development of these entrepreneurs, there areseveral advantages obtained by the use of wasted wood into creative competitiveproduct, which will increase the economic value of wasted wood, processing wastedwood will reduce the impact of the use of wood in which the supply of wood isdecreasing due to rare of wood. Utilization of wasted wood as a raw material createsethical business because trough this business we preserve the nature, not illegally takingnatural resources that increasingly scarce and taking a long time to restore it. Anotheradvantage is to expand employment opportunities and economy improvement willoccur. The development of these entrepreneurs will produce a creative competitiveproduct which would strongly support the creative economy development programpromoted by the Government of Indonesia.Keywords: Reclaimed Wood, Wasted Wood, Entrepreneur, Ethical Business